War and strategy in the modern world from Blitzkrieg to unconventional terrorism - Gat, Azar (Cass military studies, 2018)
This volume brings together some of Professor Azar Gat's most significant articles on the evolution of strategic doctrines and the transformation of war during the 20th and early 21st centuries.